Regulatory Mechanisms of Vitellogenesis in Insects - Wu, Zhongxia; Yang, Libin; He, Qiongjie; Zhou, Shutang (Frontiers in Cell and Developmental Biology, 2021)
Vitellogenesis is prerequisite to insect egg production and embryonic development after oviposition. During insect vitellogenesis, the yolk protein precursor vitellogenin (Vg) is mainly synthesized in the fat body, transported by the hemolymph through the intercellular spaces (known as patency) in the follicular epithelium to reach the membrane of maturing oocytes, and sequestered into the maturing oocytes via receptor-mediated endocytosis. Insect vitellogenesis is governed by two critical hormones, the sesquiterpenoid juvenile hormone (JH) and the ecdysteriod 20-hydroxyecdysone (20E). JH acts as the principal gonadotropic hormone to stimulate vitellogenesis in basal hemimetabolous and most holometabolous insects. 20E is critical for vitellogenesis in some hymenopterans, lepidopterans and dipterans. Furthermore, microRNA (miRNA) and nutritional (amino acid/Target of Rapamycin and insulin) pathways interplay with JH and 20E signaling cascades to control insect vitellogenesis. Revealing the regulatory mechanisms underlying insect vitellogenesis is critical for understanding insect reproduction and helpful for developing new strategies of insect pest control. Here, we outline the recent research progress in the molecular action of gonadotropic JH and 20E along with the role of microRNA (miRNA) and nutritional sensor in regulating insect vitellogenesis. We highlight the advancements in the regulatory mechanisms of insect vitellogenesis by the coordination of hormone, miRNA and nutritional signaling pathways.